(untitled) (Journal of Partial Differential Equations, 2014)
" In this paper, we consider the Cauchy problem for the model of liquid crystal. We show that if the velocity field u satisfies 2202_3u2208L^p(0,T;L^q( mathbbR^3)), frac2p+ frac3q+=1+ frac1q, 2 2039 q 2264 221e, then the solution is in fact smooth."